New alternatives to holder pasteurization in processing donor milk in human milk banks - Moro, Guido E.; Girard, Melissa; Peila, Chiara; Garcia, Nadia; Escuder-Vieco, Diana; Keller, Kristin; Cassidy, Tanya; Bertino, Enrico; Boquien, Clair-Yves; Buffin, Rachel; Calvo, Javier; Gaya, Antoni; et al. (Frontiers in Nutrition, 2024)
Infectious and toxicological risks are the main potential hazards that operators of Human Milk Banks (HMBs) encounter and must eliminate. HMBs are trying to implement procedures that allow to manage and sanitize human milk without altering significantly its nutritional and biologically protective components, obtaining a product characterized by a valid balance between safety and biological quality.The history of human milk processing is linked to the origins of HMBs themselves. And although other forms of sterilization were used originally, pasteurisation soon became the recognized most effective means for sanitizing milk: all the milk that arrives at the HMB must be pasteurised. Holder pasteurisation (HoP) is the most used methodology, and it is performed using low temperature and long time (+62.5 °C for 30 minutes).With HoP some bioactive milk components are lost to varying degrees, but many other precious bioactive compounds are completely or partially preserved.To improve the quality of human milk processed by HMBs, maintaining in the meantime the same microbiological safety offered by HoP, new technologies are under evaluation. At present, High-Temperature Short-Time pasteurisation (HTST) and High-Pressure Processing are the most studied methodologies. HTST is already utilized in some HMBs for daily practical activity and for research purposes. They seem to be superior to HoP for a better preservation of some nutritional and biologically protective components. Freeze-drying or lyophilization may have advantages for room temperature storage and transportation.The aim of this study is to evaluate the advancement regarding the processing of DHM with a literature search from 2019 to 2022. The effects of the new technologies on safety and quality of human milk are presented and discussed. The new technologies should assure microbiological safety of the final product at least at the same level as optimized HoP, with an improved preservation of the nutritional and bioactive components of raw human milk.